HUBUNGAN PENGETAHUAN DENGAN PERILAKU IBU HAMIL DALAM MENGKONSUMSI TABLET TAMBAH DARAH (FE) UNTUK MENCEGAH ANEMIA KEHAMILAN DI PUSKESMAS TANJUNG PINANG KOTA JAMBI - Iin Indrawati; Desraini Desraini2 (Universitas Baiturrahim, 2016)
Backround : From the results of the survey in Indonesia known maternal mortality rate (MMR) in Indonesia currently ranges between 300-400 maternal deaths per 100,000 live births. Indonesia's maternal mortality rate still showed a poor level of health of mothers and newborns (Puspitaningrum, 2013). The high maternal anemia affecting negatively impact the fetus from the mother during pregnancy, childbirth and postpartum which of them will be born fetus with low birth weight (LBW), premature parturition, abortion, birth defects, anemia in babies born and shock (Waryana, 2010).Method :This research is a quantitative research with cross sectional design, which is research in which variables used in the study were observed in the same time. The population in this study were all pregnant women who consume iron tablet in Puskesmas Tanjung Pinang of Jambi city, namely 920 pregnant women. The sample in this study were taken by accidental sampling technique, the research done on May 25 s/d June 18, 2015. This study used a questionnaire as a data collector and analyzed with univariate and bivariate analysis using Chi-square test.The results showed that the majority of pregnant women (51.7%) had poor knowledge, the majority of pregnant women (63.2%) had good behavior in consuming Fe tablet pregnancy to prevent anemia. Based on statistical test values obtained 0.003 P-Value α <0.05), which means there is a great relationship between knowledge relating to the behavior of pregnant women consuming Fe tablet pregnancy to prevent anemia in Puskesmas Tanjung Pinang of Jambi city in 2015.Information obtained from the results of this study can serve as a useful input in improving the knowledge and behavior of pregnant women in consuming Fe tablet.Keywords : Knowledge, Eating Behavior Tablet F